Tangled eaudiobook The junior novelization. - Disney Press (Tangled., 2014)
Get ready for lots of fun and adventure when the swashbuckling thief Flynn Rider meets Rapunzel—the girl with seventy feet of magical hair. Together they go on wild, hilarious, and heartfelt adventures when Rapunzel leaves her isolated tower for the first time.